Relationship Between the Occupational Accidents and Absence from Work Employees in Shiraz Namazi Hospital - Khalil Momenei; Jamil Sadeghifar; Zahra Kavosi; Mehdi Raadabadi; Yaser Joyani (Tehran University of Medical Sciences, 2012)
Background and Aim: An Adapting work condition with physical and mental conditions of employees is an essential factor to do the job effectively. This study was conducted to determine the relationship between employees occupational accidents and absence from work in Shiraz Namazi Hospital.Materials and Methods: This descriptive-analytical and cross-sectional study was done in Shiraz Namazi Hospital at 2010. One Hundred and sixty employees in different departments of the hospital with a random stratified sampling were enrolled in this study. Data were collected using the checklist consisting of three parts: demographic information, types of occupational accidents and three open questions to enumerate other occupational accidents, diseases resulting from occupational accidents and possible causes of exposure to this accidents. Data were analyzed using the SPSS software and using descriptive statistics and chi square & t tests.Results: Out of 160, 159 participants responded and returned the questionnaire, out of which 68.9% were females. Cuts with sharp objects (22%) and toxicity resulting from working with solvents (82%) were the lowest and highest non-exposure in sample's studies, respectively. A statistically significant relationship between gender, work shift, organizational status and duration of employment with the occurrence of a number of occupational accidents was observed.Conclusion: According to the results, there was no clear relationship between absences from work and frequency of each occupational accident. We recommend the hospitals to consider notebooks for recording occupational accidents and their way of occurrence. Also , training courses for employees shoud be in priority.